Back pain: are there solutions? - E. S. Shishkina (Лечащий Врач)
Background. Back pain remains a common and challenging medical problem. Damage to the articular-ligamentous apparatus of the spinal column is a source of both nonspecific and specific causes of pain. The universal treatment for patients with back pain is the prescription of chondroprotectors, the undisputed leader among which is chondroitin sulfate.Objective. Evaluation of the effectiveness and safety of drug therapy from their group of delayed-acting symptom-modifying drugs in patients with back pain when used for 20 days.Materials and methods. The study included 30 patients diagnosed with dorsopathy with acute or chronic pain syndrome. Patients received a modern injection chondroprotector consisting of a complex of polypeptides, mucopolysaccharides (chondroitin sulfate), amino acids, sodium, potassium, magnesium, iron, copper, zinc, 2 ml every other day for 20 days according to the instructions for medical use of the drug. Before and after 30 ± 5 days from the start of treatment, a comprehensive examination of patients was carried out with an assessment of the severity of pain on a 100-mm visual analogue scale, a general assessment of the patient’s health status on a visual analogue scale, an assessment of satisfaction with therapy on a visual analogue scale, and the level of anxiety-depressive disorders on hospital HADS scale, sleep disturbances according to the insomnia severity scale. The criterion for analyzing the effectiveness was the degree of pain control assessed by the subjects on a visual analogue scale 30 ± 5 days from the start of treatment (10 days after completion of the course) compared with the initial value.Results. Significant positive dynamics were observed among patients with back pain. Initially, the pain was 84 mm; after 30 ± 5 days from the start of treatment, the pain decreased to 23.33 mm (p < 0.05). The patient's overall health assessment on the visual analogue scale increased from 55 to 86.67 mm (p < 0.05). Patients rated their satisfaction with the therapy highly: from 29 to 91.33 mm (p < 0.05). There were no cases of serious adverse events. A decrease in the severity of affective disorders (anxiety-depressive syndrome and insomnia) was recorded during treatment (anxiety by 3.5 times, depression by 1.3 times and insomnia by 2 times) (p < 0.05). Conclusions: drug therapy in patients with back pain can achieve a statistically significant reduction in the severity of pain and improvement in the affective component in most patients. The therapy is characterized by a high safety profile and good tolerability.